Biochar-assisted copper removal and metabolic responses of Hydrocotyle vulgaris in a hydroponic system: Insights from untargeted metabolomics and computational modeling - Ziyi Lian; Xiaofan Fu; Haoran Yin; Yuxin Li; Lei Zhao; Jing Shang; Tian Gao; Bo Zhang; Chengbin Xu; Runjie Zhang; Fang Ma; Jieting Wu (Journal of Environmental Management, 2026)

AI-assisted SERS fingerprint of serum omics analysis for precision breast cancer screening - Lingna Wang; Weihua Hong; Jinyong Lin; Chengbin Fu; Yuanmei Chen; Zeyang Liu; Min Fan; Luyun Xu; Jianqing Ye; Chengtao Ruan; Chaobin Huang; Xueliang Lin; et al. (Chemical Engineering Journal, 2025)

Unraveling histones: plant protectors under environmental stress unlocking the key to resilience - Jieting Wu; Jing Shang; Lei Zhao; Xiaofan Fu; Jin Lv; Sidi Lv; Chengbin Xv; Wenquan Jin; Junsheng Lv; Fang Ma; Haijuan Guo (Plant and Soil, 2025)

Interlayer manipulation of bio-inspired Ti3C2Tx nanocontainer through intercalation of amino acid molecules to dramatically boosting uranyl hijacking capability from seawater - Chang Liu; Ye Li; Miao Lei; Dongxue Liu; Bolin Li; Chengbin Fu; Junpeng Guo (Journal of Hazardous Materials, 2024)

LncRNA activates immune response against Vibrio anguillarum in the intestine-liver axis of turbot (Scophthalmus maximus L.) by sponging miRNA in a ceRNA regulatory network - Xin Cai; Chengbin Gao; Alan J. Lymbery; Le Ma; Qiang Fu; Ranran Huang; Chao Li (Aquaculture, 2023)

In suit establishment of Ti3C2 MXenes exchanger via Na+, K+ and NH4+ intercalation: Exceptionally UO22+ loading capability and hijacking mechanism - Chang Liu; Ye Li; Dongxue Liu; Miao Lei; Bolin Li; Chengbin Fu; Jun Zhang (Chemical Engineering Journal, 2023)

Constructing of a stable Ti3C2 MXenes nano-traps with ultrahigh and selectively uranyl encapsulation capability by polyethyleneimine intercalation - Chang Liu; Ye Li; Dongxue Liu; Miao Lei; Bolin Li; Chengbin Fu; Jun Zhang (Chemical Engineering Journal, 2023)

A universal strategy for large-scale and controlled fabrication of conductive mesoporous polymer monolayers - Facai Wei; Bowen Chen; Jianwei Fu; Qingguo He; Chengbin Jing; Jiangong Cheng; Miharu Eguchi; Jongbeom Na; Yusuke Yamauchi; Shaohua Liu (Chemical Engineering Journal, 2023)

Synthesis of Lanthanum-Modified Attapulgite and Its Phosphorus-Fixing Mechanism for Urban Eutrophic Lake - Lingfeng Ye; Ye Li; Cong Liu; Bolin Li; Dongxue Liu; Chang Liu; Jie Wan; Chengbin Fu (Water, Air, & Soil Pollution, 2022)

Comparative Transcriptome Analysis of Spleen Reveals Potential Regulation of Genes and Immune Pathways Following Administration of Aeromonas salmonicida subsp. masoucida Vaccine in Atlantic Salmon (Salmo salar) - Qiang Fu; Yuqing Li; Hao Zhang; Min Cao; Lu Zhang; Chengbin Gao; Xin Cai; Defeng Chen; Ziying Yang; Jie Li; Ning Yang; Chao Li (Marine Biotechnology, 2022)

A community effort to assess and improve computerized interpretation of 12-lead resting electrocardiogram - Zijian Ding; Guijin Wang; Huazhong Yang; Ping Zhang; Dapeng Fu; Zhen Yang; Xinkang Wang; Xia Wang; Zhourui Xia; Chiming Zhang; Wenjie Cai; Binhang Yuan; et al. (Medical & Biological Engineering & Computing, 2022)
Computerized interpretation of electrocardiogram plays an important role in daily cardiovascular healthcare. However, inaccurate interpretations lead to misdiagnoses and delay proper treatments. In this work, we built a high-quality Chinese 12-lead resting electrocardiogram dataset with 15,357 records, and called for a community effort to improve the performances of CIE through the China ECG AI Contest 2019. This dataset covers most types of ECG interpretations, including the normal type, 8 common abnormal types, and the other type which includes both uncommon abnormal and noise signals. Based on the Contest, we systematically assessed and analyzed a set of top-performing methods, most of which are deep neural networks, with both their commonalities and characteristics. This study establishes the benchmarks for computerized interpretation of 12-lead resting electrocardiogram and provides insights for the development of new methods.

Equivalent effect of extracellular proteins and polysaccharides on biofilm formation by clinical isolates of Staphylococcus lugdunensis - Weidong Qian; Wenjing Wang; Jianing Zhang; Miao Liu; Yuting Fu; Mingming Li; Jing Jin; Wei Cui; Chengbin Wang (Biofouling, 2021)

Dynamics of MiRNA Transcriptome in Turbot (Scophthalmus maximus L.) Intestine Following Vibrio anguillarum Infection - Chengbin Gao; Xin Cai; Qiang Fu; Ning Yang; Lin Song; Baofeng Su; Fenghua Tan; Baining Liu; Chao Li (Marine Biotechnology, 2019)

Paragonimus skrjabini Chen, 1959 (Digenea: Paragonimidae) and related species in eastern Asia: a combined molecular and morphological approach to identification and taxonomy - David Blair; Chang Zhengshan; Chen Minggang; Cui Aili; Wu Bo; Takeshi Agatsuma; Moritoshi Iwagami; David Corlis; Fu Chengbin; Zhan Ximei (Systematic Parasitology, 2005)